2007
DOI: 10.1093/jnci/djm069
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Specificity of Loss of Imprinting of the IGF2 Gene in Wilms Tumors

Abstract: Loss of imprinting (LOI) of the IGF2 gene (which encodes insulin-like growth factor II) is the most common genetic or epigenetic alteration in Wilms tumor; LOI involves aberrant activation of the normally repressed maternally inherited allele. We found previously that LOI of IGF2 occurs in approximately half of all Wilms tumors (i.e., those arising from lineage-committed nephrogenic progenitor cells). We investigated whether LOI of IGF2 is associated with relaxation of imprinting at loci other than IGF2 or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 21 publications
(30 reference statements)
6
51
2
1
Order By: Relevance
“…However, there is evidence to suggest that alterations in DMR methylation are specific for the IGF2/H19 locus in case of WTs (14,15,29). Nevertheless, our data broadens this concept by clearly documenting that transcriptional activation of imprinted genes is a common finding in WTs and imprinted genes are activated as functional units.…”
Section: B Dsupporting
confidence: 50%
See 1 more Smart Citation
“…However, there is evidence to suggest that alterations in DMR methylation are specific for the IGF2/H19 locus in case of WTs (14,15,29). Nevertheless, our data broadens this concept by clearly documenting that transcriptional activation of imprinted genes is a common finding in WTs and imprinted genes are activated as functional units.…”
Section: B Dsupporting
confidence: 50%
“…To see whether widespread activation of imprinted genes in WTs depends on epigenetic changes, we analyzed the methylation status of H19DMR and made correlations with the expression level of imprinted genes. H19DMR has been chosen, as deregulation of the IGF2/H19 cluster is a wellknown mechanism described in many embryonal cancers (12,14,29). By using a quantitative real-time PCR-based method (14) we depicted that two-thirds of all WTs displayed alterations at this locus.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…These include reports that have excluded imprinting defects in the 14q DLK1/GTL2 imprinting cluster in WT (45,46) and a study of allele-specific expression and methylation of imprinted genes in 11p15 LOI WTs, which showed that the only major alterations were confined to the IGF2/H19 region (47). However, the study we report here represents the first to directly compare two different loci that each show LOI in WT.…”
Section: Loi At 11p15mentioning
confidence: 86%
“…Through proliferation, this clone became the only hemopoietic cell in the bone marrow and peripheral blood and resulted in the β-thalassemia major phenotype, a phenomenon found in a variety of malignancies. 16,17 We conclude that the patient's β-thalassemia major involved inheritance of paternal uniparental isodisomy of chromosome 11p15 harboring the HBB [c.52A>T] allele, which was mixed with β-thalassemia minor mosaicism caused by normal biparental inheritance. Though homozygosity of autosomal recessive gene mutations was described in uniparental disomy of other chromosomes, homozygosity of HBB gene mutations associated with paternal uniparental isodisomy of 11p15 is reported here for the first time.…”
Section: Resultsmentioning
confidence: 94%